A bidirectional electrocatalyst for enhancing Li2S nucleation and decomposition kinetics in lithium–sulfur batteries. Issue 34 (9th August 2022) - Ren, Yilun; Chang, Shaozhong; Hu, Libing; Wang, Biao; Sun, Dongyue; Wu, Hao; Ma, Yujie; Yang, Yurong; Tang, Shaochun; Meng, Xiangkang
Abstract : Well-dispersed (NiCo)0.85 Se nanoparticles embedded in Ti3 C2 nanosheets are developed. The Ti3 C2 /(NiCo)0.85 Se heterostructure is demonstrated as a bidirectional electrocatalyst and endows Li–S batteries with an ultrastable lifespan. Abstract : Accelerating sulfur redox reactions and suppressing the shuttle effect of lithium polysulfide (LiPSs) are crucial for high-performance lithium–sulfur (Li–S) batteries. Herein, we develop a highly efficient bidirectional electrocatalyst (Ti3 C2 /(NiCo)0.85 Se) consisting of 2D Ti3 C2 nanosheets loaded with well-dispersed (NiCo)0.85 Se nanoparticles. Based on electrochemical analysis and theoretical calculations, the Ti3 C2 /(NiCo)0.85 Se heterostructure is demonstrated to provide abundant active sites for steady bidirectional electrocatalysis and abundant lithiophilic–sulfiphilic anchoring points for the immobilization of LiPSs. Ti3 C2 promotes the reduction process of LiPSs to Li2 S, and (NiCo)0.85 Se enhances the decomposition of Li2 S. Moreover, the (NiCo)0.85 Se nanoparticles prevent the Ti3 C2 nanosheets from aggregating, ensuring a hierarchical porous framework endowed with good structural robustness and fast electron/ion transportation. Li–S batteries with Ti3 C2 /(NiCo)0.85 Se modified separators exhibit an ultralong cycling lifespan with a capacity decay rate of only 0.03% per cycle over 2000 cycles at 1C and improved rate capability. When equipped with a high sulfur loading of 6.4 mg cm −2 and a low electrolyte/sulfur ratio of 8 μL mg −1, the cell maintains a distinguished area capacity of 9.7 mA h cm −2 . This work provides a general strategy for the design of bidirectional electrocatalysts for high-performance Li–S batteries with especially remarkable cycling stability.